Law no. 5,692 of 1971 and the Education Guidelines and Basics Law no. 9,394 of 1996: approaches and distances in the organization of education in basic education (Research, Society and Development, 2020)
The laws that regulate Brazilian education have undergone several changes over the past decades. In this article we have the objective of analyzing the approaches and distances between the organization of education with emphasis on professional education that are provided in Law No. 5,692 of 1971 and the Law of Guidelines and Bases of Education No. 9,394 of 1996 (LDB/96). The period between 1971 and 1996 is justified because Law nº 5.692/71 lasted from 1971, during the military regime, until 1996 when it was revoked during the re-democratization period by LDB/96. The study proposed here is based on bibliographic review and documentary analysis. In view of the above, we have two questions: How was teaching organized in levels and modalities in Law nº 5.692/71 and LDB/96 in the year of its promulgation? What are the approximations and possible distances in the organization of professional education between the two laws? The research points out several aspects, among which we can conclude that the organization of teaching in Law nº 5.692/71 and in LDB/96 in the year of its promulgation is approaching in several ways: length of time for the levels of teaching, free teaching of 1st degree, current elementary education. The number of school days is also approximate, with a difference of only 20 days between the two legislations. As a distance, we identified that in Law 5.692/71 there was a greater emphasis on training for the labor market, while in LDB/96 a more human-oriented view.